KONTRIBUSI ARTHROPODA KANOPI DALAM MENJAGA STABILITAS EKOSISTEM PADA KEBUN BERBASIS SENGON LAUT (Paraserianthes falcataria (L.) BUDIDAYA PORANG (Amorphophallus muelleri Blumei) (Schott) DI JEMBER SEBAGAI SUMBER BELAJAR BIOLOGI - Budiharto, Ivone Wulandari (BIOEDUKASI (Jurnal Pendidikan Biologi), 2012)
The development of agroforestry based of Sengon Laut with Porang crop area has successfully to increase people economic level. This research aimed to analyze and compare diversity, composition, structure community of canopy Arthropod at two different location (Sengon Laut of Porang crop area and non porang crop area) which was attracted to blue and yellow colored water pan trap,  vertical variation diversity, abundance, and structure community of canopy Arthropod, to know the relation between community of Arthropod canopy with abiotic factor at local agroforestry and to recommend good cultivating management. Samples of canopy Arthropod was taken at two different location by blue and yellow colored water pan trap, which was hang on bottom layer (1-1,5 m) and upper layer (8-10 m). Abiotic factors (Temperature and light intensity) were measured at each location. Non crop vegetation was analyzed by line intercept method and tree vegetation was analyzed by complete count method. Data of structure community comparison each location was analyzed by important value and diversity (Index Shannon-Whienner). The degree of same level composition between two location was analyzed by Index Bray-Curtis and variation vertical analyzed by anova. Canopy Arthropod composition and relation with abiotic factors was analyzed by Pearson Correlation with MINITAP program. The value abundance of canopy Arthropod in Porang crop area was (329 individu), fewer than canopy Arthropod in non Porang crop area which was (829 individu). The result showed that yellow water pan trap had better efficiency on upper layer at non Porang crop area than porang crop area. Recommendation to the farmers in order to make good cultivation management non crop vegetation is not cleaned and not used pesticide utilization. Kata kunci:  Arthropoda kanopi, faktor abiotik,  stabilitas ekosistem, sengon laut, budidaya porang